BEFORE OPERATING ROOM NURSING JOURNALS: OPERATING ROOM NURSING IN THE PAGES OF THE CANADIAN NURSE 1940-1960 - Moszczynski, Alice (Operating Room Nurses Association of Canada Journal, 2010)
The Canadian Nurses Association (CNA) values learning from nursing history to provide a contextual perspective in understanding how past events have shaped current nursing practice. Until the publication of operating room nursing journals, Canada’s national nursing journal, The Canadian Nurse, served as an educational and professional resource for those nurses working in the operating room and for nurses whose work was related to, or connected with, the operating room. A historical review of early issues of The Canadian Nurse (first published in 1905) reveals a substantial amount of content related to operating room nursing in the twenty year period, beginning in the 1940s, that predated the existence of OR specialty journals. The content was, for the time, both detailed and informative. It was through this journal that operating room nurses, indeed all Canadian nurses, learned about new advances, employment opportunities, educational programs, professional associations, and the achievements of those in the profession. Operating Room Nursing, as an isolated and quickly emerging specialty, was introduced to other nurses via items in The Canadian Nurse journal.